1994
DOI: 10.1111/j.1532-5415.1994.tb06076.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin‐Like Growth Factor I in Healthy Older Men in Relation to Physical Activity

Abstract: The data do not support the hypothesis that lack of physical activity is responsible for the decline in serum IGF-I with advancing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The relationship of physical activity and IGF levels has been similarly inconsistent. Most studies, like our own, found no association [14,22,28,44,50], although others observed inverse [35] or positive [25,51] associations. The relationship between physical activity and IGF levels is complex.…”
Section: Anthropometry and Physical Activitymentioning
confidence: 78%
See 1 more Smart Citation
“…The relationship of physical activity and IGF levels has been similarly inconsistent. Most studies, like our own, found no association [14,22,28,44,50], although others observed inverse [35] or positive [25,51] associations. The relationship between physical activity and IGF levels is complex.…”
Section: Anthropometry and Physical Activitymentioning
confidence: 78%
“…These included demographics (age, sex, and race) [22-27, 30, 33, 41], anthropometrics (height, BMI) [14,22,23,25,26,28,[30][31][32][42][43][44][45][46][47][48][49], recent vigorous physical activity [14,22,25,28,35,44,50,51], smoking [22, 25-28, 30, 32, 47], reproductive factors [25][26][27][28], and milk consumption [38,52,53], as well as some that have not specifically been evaluated (aspirin/NSAIDs use, multivitamin and calcium supplement use). Data were analyzed using multivariate linear regression to evaluate the association between lifestyle (independent variables) and circulating IGF-1, IGFBP-3, and their molar ratio (dependent variables).…”
Section: Analysesmentioning
confidence: 99%
“…Furthermore, although there are no data available on a possibly age-dependent decline in paracrine secretion of IGF-1, it is a matter of fact that the humoral concentration of IGF-1 is drastically decreased by aging [31] . Therefore it could be that the role of IGF-1 is progressively assumed by insulin as age advances as its secretion progressively increases in adult age [32] .…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between tIGF-I and fitness was later suggested in a study where physically active elderly were compared with sedentary elderly, but fitness and energy expenditure were not assessed [56]. More recently, Eliakim et al have demonstrated a positive correlation between tIGF-I and VO 2 max in pre-pubertal girls [57], while this apparent relationship did not reach significance in adolescent girls [58].…”
Section: Effects Of Training On Tigf-i Concentrationsmentioning
confidence: 99%